Strategic Integration of Artificial Intelligence and Innovation Management for Enhancing Organizational Performance: The Moderating Role of Organizational Agility - Babatunde, Bayode Olusanya; Olaleye, Banji Ridwan; Fasanmi, Olumuyiwa Oladapo; Ayodele, Ademola Emmanuel; Oshatimi, Omowumi Olanike (International Review of Management and Marketing, 2025)
The study examined the impact of strategic integration of artificial intelligence (SAI) and innovation management (OI) on organizational performance (OP) with the moderating role of organizational agility (OA) to determine how strategic integration of artificial intelligence influences organizational performance (OP). Furthermore, the extent to which strategic artificial intelligence-driven influences on organizational agility was also examined. This study employed a quantitative approach with a targeted 250 respondents from the population, which consisted of ten (10) selected top deposit money banks presently operating in Lagos State, Nigeria, using a purposive sampling technique. Partial Least Square-Structural Equation Modeling (PLS-SEM) was utilized to assess the structural model and test the hypothesized relationships among the variables captured. First, the study revealed that SAI significantly influences both OA and OP (0.627 and 0.583, respectively). IM has shown a strong effect on both agility (0.697) and organizational performance (0.873). Moreover, the finding revealed that the mediating role of OA had a moderate influence on OP. The indirect effect of innovation management on performance via agility is weak (0.006); SAI had a more substantial indirect effect on performance through agility (0.039), highlighting the importance of agility in enabling the adaptability required for AI-driven success. SAI had a significant total effect on organizational agility (0.627) and performance (0.622), revealing its importance as a core component of modern business strategy. The study concluded that strategic integration of artificial intelligence influences organizational agility and organizational performance positively. Innovation management maintains a strong positive relationship with organizational performance, and organizational agility plays a slight role in mediating the relationship among strategic integration of artificial intelligence, innovation management, and organizational performance. The finding stresses the importance of strategically integrating artificial intelligence with innovation management to optimize organizational agility and, ultimately, enhance performance in dynamic environments. The study recommends that managers should align operations with strategic artificial intelligence, adopt modern technologies, and invest more in innovative practices to improve efficiency and sustainability.